Recurrent invasive liver abscess syndrome induced by Klebsiella pneumoniae with emerging drug resistance: a case report and literature review - Yongmei Li; Zheng He; Fengjiao Wu; Jialin Li; Chengcheng Wang (Frontiers in Medicine)
BackgroundInvasive liver abscess syndrome (ILAS) caused by hypervirulent Klebsiella pneumoniae (hvKp) is a life-threatening infection associated with high mortality, particularly when complicated by brain abscesses. The emergence of carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKp) during treatment, driven by emerging resistance, poses significant therapeutic challenges.Case presentationWe describe a 70-year-old diabetic male with recurrent ILAS who developed sequential multi-organ infections, including urinary tract infection, bacteremia, lung abscess, and brain abscess. Initial isolates were identified as carbapenem-susceptible; however, under prolonged antimicrobial pressure, they were transformed into CR-hvKp carrying the KPC gene. Treatment escalated from meropenem to ceftazidime-avibactam plus tigecycline, resulting in clinical improvement and discharge after 48 days.ConclusionThis case highlights the critical challenge of emerging resistance in hvKp during prolonged therapy, emphasizing the need for early molecular surveillance, multidisciplinary collaboration, and optimized antibiotic stewardship to mitigate treatment failure in ILAS.